2013
DOI: 10.1186/1756-3305-6-103
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection with Anaplasma platys, Bartonella henselae and Candidatus Mycoplasma haematoparvum in a veterinarian

Abstract: BackgroundDuring a two year period, a 27-year-old female veterinarian experienced migraine headaches, seizures, including status epilepticus, and other neurological and neurocognitive abnormalities. Prior to and during her illness, she had been actively involved in hospital-based work treating domestic animals, primarily cats and dogs, in Grenada and Ireland and anatomical research requiring the dissection of wild animals (including lions, giraffe, rabbits, mongoose, and other animals), mostly in South Africa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(143 citation statements)
references
References 40 publications
7
130
0
6
Order By: Relevance
“…Although contact with saliva was not confirmed as a risk factor for infection, a study by Sazaki et al (2008) showed that dogs of the Tosa breed, which are usually known as fighting dogs, are more prone to infection in Japan. Maggi et al (2013) Immunosuppression and weakness caused by other concomitant diseases have been identified as important factors that favor infection by these agents (PRYOR & BRADBURY, 1975;KRAKOWKA, 1977;GRETILLAT, 1981;NOVACCO et al, 2010;ROURA et al, 2010). In Brazil, coinfections by M. haemocanis and other tick-borne pathogens in dogs have also been reported (TRAPP et al, 2006;RAMOS et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although contact with saliva was not confirmed as a risk factor for infection, a study by Sazaki et al (2008) showed that dogs of the Tosa breed, which are usually known as fighting dogs, are more prone to infection in Japan. Maggi et al (2013) Immunosuppression and weakness caused by other concomitant diseases have been identified as important factors that favor infection by these agents (PRYOR & BRADBURY, 1975;KRAKOWKA, 1977;GRETILLAT, 1981;NOVACCO et al, 2010;ROURA et al, 2010). In Brazil, coinfections by M. haemocanis and other tick-borne pathogens in dogs have also been reported (TRAPP et al, 2006;RAMOS et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…ticks, fleas, lice, mites, flies and mosquitoes) have been identified as vectors of numerous species of hemoplasmas in different vertebrate hosts (Table 1). Most of them are known to infest different species and represent a possible interspecific transmission vector, as probably occurred in animal-origin human mycoplasmosis (SANTOS et al, 2008;MAGGI et al, 2013). Therefore, it is mandatory to investigate the vector competence of other arthropods in relation to hemotropic mycoplasmas transmission to dogs, since the importance of the R. sanguineus tick remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…En el caso de A. platys, en Venezuela se ha identificado la presencia de mórulas compatibles en el citoplasma de plaquetas de pacientes con seropositividad al virus de la inmunodeficiencia humana 38 y también se detectó mediante RPC en un veterinario con síndrome febril y co-morbilidades 39 . Sin embargo, se necesitan estudios complementarios para confirmar su rol como agente zoonótico.…”
Section: Artículo Originalunclassified
“…For example, co-infection of a female veterinarian by Bartonella henselae, Anaplasma platys, and Candidatus Mycoplasma haematoparvum was reported recently and, importantly in this context, the latter two organisms were known previously to only infect dogs [62]. The emergence of infectious viral hepatitis and HIV resulted in the universal adoption of comprehensive protective practices within the human medical community [63]; maybe this case should serve as a reminder that there is much to understand about risks to veterinarians, and this paradigm calls for a cultural change in work practices and attitudes in regard to vector-borne infections [61].…”
Section: Paradigm 4: Cvbd Veterinarians and Public Healthmentioning
confidence: 98%